-7v+6=-6v

Simple and best practice solution for -7v+6=-6v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7v+6=-6v equation:


Simplifying
-7v + 6 = -6v

Reorder the terms:
6 + -7v = -6v

Solving
6 + -7v = -6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '6v' to each side of the equation.
6 + -7v + 6v = -6v + 6v

Combine like terms: -7v + 6v = -1v
6 + -1v = -6v + 6v

Combine like terms: -6v + 6v = 0
6 + -1v = 0

Add '-6' to each side of the equation.
6 + -6 + -1v = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -1v = 0 + -6
-1v = 0 + -6

Combine like terms: 0 + -6 = -6
-1v = -6

Divide each side by '-1'.
v = 6

Simplifying
v = 6

See similar equations:

| 2+4x=8+x | | -12x+20=-x^2 | | 10-6j=-5j | | 3m^2-11m-20=0 | | 5x-10=4x+11 | | -52+10x=68 | | 4(4x+1)=3x-4(6-x)+3 | | 14p+q+4p+17q= | | -8q=-7q+10 | | 52-31=x | | -37+7x=40 | | s^3+3s^2+3s+1=0 | | s^3+4s^2+4s+1=0 | | 6x+12=-84+10x | | 12x-42=114 | | 13-6x=5-8x | | 7p-(3+4)=-2(2p-1)+10 | | 5(x-4)+3-9x=6-(2x+5)+8x | | 56+8x=128 | | 5x-2(x+1)=9 | | -16t^2+16t^2+896= | | 53-10x=17+8x | | 4x-44=0 | | -17r=-170 | | 4x+83=-7 | | 11x+1=12-4 | | z-20=15 | | 15(y-4)= | | 85000=.9x | | 3x-4(2x+1)=-(x-3)+6x+8 | | 7-7x-3x=37 | | 31=-8(5x-4) |

Equations solver categories